2021
DOI: 10.1080/08870446.2021.1960987
|View full text |Cite
|
Sign up to set email alerts
|

Viral mitigation and the COVID-19 pandemic: factors associated with adherence to social distancing protocols and hygienic behaviour

Abstract: Objective: To investigate the factors associated with adherence to viral mitigation protocols during the COVID-19 pandemic. Design: This epidemiological cross-sectional study examines adherence to behaviour in 4158 adults and its relationship with sources of information. Main outcome measures: Adherence to social distancing protocols (SDPs) and adherence to hygienic behaviour (HB) recommendations. Results: Individuals aged 18-30 reported lowest adherence to SDPs and HB. Alcohol consumption was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…This was followed closely by the provision of reminders as a nudging tool. Between the publication of the meta-analysis and the current study, other financial nudging studies have been few and far between, with most research focusing on health-related behaviours surrounding the pandemic (e.g., social distancing [39]; vaccination [40]; hand hygiene [41]). Empirical nudging studies on financial behaviour since the 2019 meta-analysis are scarce, although some do exist (e.g., choice architecture in retirement plans [42]; reminders for credit card payments [43]; information provision for credit card payments [44]).…”
Section: Literaturementioning
confidence: 99%
“…This was followed closely by the provision of reminders as a nudging tool. Between the publication of the meta-analysis and the current study, other financial nudging studies have been few and far between, with most research focusing on health-related behaviours surrounding the pandemic (e.g., social distancing [39]; vaccination [40]; hand hygiene [41]). Empirical nudging studies on financial behaviour since the 2019 meta-analysis are scarce, although some do exist (e.g., choice architecture in retirement plans [42]; reminders for credit card payments [43]; information provision for credit card payments [44]).…”
Section: Literaturementioning
confidence: 99%
“…While our work strongly suggests that the adoption of economic shutdown measures in BC is, in the long term, a responsible strategy, the shutdown in BC has caused a significant increase in deaths due to drug overdoses there [34]; the excess (total overdose deaths over and above the usual average) for March to June 2020, exceeds the total number of COVID-19 deaths for that time period by over 40% [34,35]. A number of factors are probably involved in this mortality, including the disruption of regular drug supply chains, through border closures, leading to an increasingly toxic drug supply [36], the reduction in access to harm reduction services as a result of physical distancing protocols [36], and increased stress resulting from increased isolation and economic uncertainty [37][38][39] (similar patterns have been observed in the USA [40]). The value of these lost lives could have a significant effect on our cost calculations, but assessing the relation between the level of economic shutdown and the number of overdose deaths is not straightforward.…”
Section: Other Costsmentioning
confidence: 99%
“…Finally, mental health, in general, is known to suffer during community disasters [47,48], including pandemics. Research is emerging regarding the effects of COVID-19 nonpharmaceutical measures on mental health [37][38][39]49,50], but costs are difficult to determine at this stage.…”
Section: Other Costsmentioning
confidence: 99%
“…Against this backdrop, addiction medicine specialists have reported that BD cases have increased in Japan during the pandemic ( Calvey et al, 2020 ). This may have important public health implications not only because the prevalence of BD was already high in Japan before the coronavirus pandemic began ( Bergmark and Kuendig, 2008 , World Health Organisation, 2018 ) but also because recent research from other countries has shown that increased alcohol consumption ( Ebrahimi et al, 2021 ), BD ( Einberger et al, 2021 , Suffoletto et al, 2020 ) and alcohol abuse ( Taylor et al, 2021 ) are all linked to non-compliance with COVID-19 preventive measures. Together with other research that has linked alcohol consumption to symptomatic (vs. asymptomatic) COVID-19 infection ( Saurabh et al, 2021 ), SARS-CoV-2 seropositivity and a self-reported infection history ( Kianersi et al, 2021 ) and an increased risk for developing acute respiratory distress syndrome (ARDS) when hospitalized for COVID-19 ( Lassen et al, 2021 ), this highlights the importance of research focused on alcohol use and misuse during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%